The implications of public debt for the Polish economy in XXI century - Pach, Janina (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
Public debt, which is largely a consequence of budget deficit, is a quite common problem inthe world. This is related to the discontinuation of balanced budget policy as the fundamental principle.However, the crisis of 2008 confirmed that budget deficit may cause a serious threat to financialsecurity, economic growth and development of countries. This is due to the fact that public debt isassociated with costs of servicing as well as a number of risks such as credit risk, risk of liquidity, riskof refinancing, etc.The article is an attempt to answer following research question: What is a budget deficit and its nature? What is the essence and source of public debt? What are the limits of public debt in theory and economic practice? When and why public debt becomes a threat to the country’s economy? What is the size and structure of the Polish public debt compared to selected European Union countries? What is the sense of debt management? Responses to the questions above will help diagnose the consequences of public debt for Polish economyand the directions of its impact.